Current scenario of and future perspective for scientific research in Nepal - Acharya, Krishna Prasad (Heliyon, 2020)
Scientific research can act as the 'bedrock for development' which can provide a solid foundation for the overall socioeconomic transformation in a country through invention and innovation. The inclusion of seven groups of Nepalese monuments in the United Nations Educational, Scientific and Cultural Organization (UNESCO)'s world heritage sites provides evidence of the richness in architecture and civil engineering in the country, which also show how Nepal was influenced by arts and religious philosophy. The government of Nepal (GoN) has established different scientific departments, universities, and research institutions, and has tried to emphasize the application of science and research for the development of the nation. These institutions, however, have inadequate resources, exist in a poor academic and research environment and are subject to overt political influence. Despite these various problems, a variety of pioneer research and development activities have been conducted, which show positive rays of hope. This review presents history, current situation, progress and future perspective for scientific research and development in Nepal.